INFLUENCE OF PRICE AND BRAND IMAGE ON DECISION TO PURCHASE MS GLOW SKINCARE - Nur Mutiah Tanjung (KOLONI, 2022)
This research was conducted with the aim of knowing that there was an effect of price and brand image on purchasing decisions for MS Glow skincare for female students of the Islamic Economics Study Program, Faculty of Islamic Economics and Business, UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan. This research is a quantitative research. The sample used in this study were 54 people. Data collection techniques using questionnaires, interviews and documentation. Analysis using statistics, namely SPSS version 23. Data analysis techniques with partial test (t), simultaneous test (F), coefficient of determination test (R2). The results of the study stated that there was an effect of price on purchasing decisions for MS Glow skincare for female students of the Islamic Economics Study Program, Faculty of Islamic Economics and Business, UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan. Then there is the influence of brand image on purchasing decisions for MS Glow skincare for Islamic Economics Study Program students, Faculty of Islamic Economics and Business UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan. Meanwhile, simultaneously there is the influence of price and brand image on purchasing decisions for MS Glow skincare in Islamic Economics Study Program students, Faculty of Islamic Economics and Business, UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan.  Keywords: Brand Image, Price, Purchase Decision.